2016
DOI: 10.1074/jbc.m116.735720
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elements in the Gαs and Gαq C Termini That Mediate Selective G Protein-coupled Receptor (GPCR) Signaling

Abstract: Although the importance of the C terminus of the ␣ subunit of the heterotrimeric G protein in G protein-coupled receptor (GPCR)-G protein pairing is well established, the structural basis of selective interactions remains unknown. Here, we combine live cell FRET-based measurements and molecular dynamics simulations of the interaction between the GPCR and a peptide derived from the C terminus of the G␣ subunit (G␣ peptide) to dissect the molecular mechanisms of G protein selectivity. We observe a direct link be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 53 publications
2
60
0
Order By: Relevance
“…). Based on similar Fluorescence Resonance Energy Transfer‐based SPASM sensors for other GPCRs (28, 40) and structural insights into the mechanisms of interactions between GPCRs and G proteins a subunits (712) we anticipated that following construct expression agonist‐induced engagement of the G protein segment with the receptor would result in enhanced BRET signal. We cloned these sensors into Flp‐In T‐REx 293 cells and, following doxycycline‐induced expression, studied initially the kinetics of response of the Gα 13 ‐containing sensor upon addition of zaprinast.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…). Based on similar Fluorescence Resonance Energy Transfer‐based SPASM sensors for other GPCRs (28, 40) and structural insights into the mechanisms of interactions between GPCRs and G proteins a subunits (712) we anticipated that following construct expression agonist‐induced engagement of the G protein segment with the receptor would result in enhanced BRET signal. We cloned these sensors into Flp‐In T‐REx 293 cells and, following doxycycline‐induced expression, studied initially the kinetics of response of the Gα 13 ‐containing sensor upon addition of zaprinast.…”
Section: Resultsmentioning
confidence: 99%
“…Certain GPCRs do, however, appear to display considerable selectivity for G 12 /G 13 over other G proteins, and in the case of the nominally orphan receptor GPR35 it has been suggested that there is even marked selectivity for G 13 over G 12 (49). To assess this in a controlled and potentially quantitative manner, we established a range of SPASM sensors (28, 40) in which hGPR35a was linked to the C‐terminal 27 aa of various G protein α subunits via a flexible linker in which receptor interaction with the G protein segment results in enhanced BRET signal. A variant NP form, lacking the G protein segment, did not result in altered BRET with addition of various agonists at hGPR35, demonstrating that the G protein segment was indeed required for signal alteration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seminal works have shed light on the critical involvement of GPCR intracellular (IC) loops and the transmembrane (TM) helix 6 (TM6) interface in mediating selective G-protein interactions (19)(20)(21)(22)(23). Analysis of 3D structures combined with previous cell-based assay studies show the α5 helix in the C terminus of the Gα protein exhibits a large effect on selective coupling to GPCRs (24)(25)(26)(27)(28)(29). Here we study the dynamic interactions of the C terminus of Gα s , Gα i , and Gα q proteins, hereafter referred to as s-pep, i-pep, and q-pep, in combination with seven class A GPCRs (β2-Adrenergic Receptor, β 2 AR; β3-Adrenergic Receptor, β 3 AR; Dopamine 1 Receptor, D 1 R; α2A-Adrenergic Receptor, α 2A AR; Cannabinoid 1 Receptor, CB 1 R; α1A-Adrenergic Receptor, α 1A AR; and Vasopressin 1A Receptor, V 1A R), to delineate the GPCR−G-protein selectivity determinants.…”
mentioning
confidence: 99%